Implications of behavioural economics for public regulation: An experimental study among officials of regulatory bodies in Poland - Szkudlarek, Piotr (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: Identification and determination of the importance of behavioural factors in public regulation. The study also delved into whether officials working in public regulatory bodies exhibit behavioural patterns similar to those of non-officials when making regulatory decisions. Methodology: The author used the results from experimental studies conducted among officials from regulatory bodies in Poland, specifically the Office of Electronic Communications (OEC, n = 107) and the Energy Regulatory Office (ERO, n = 157). A control group comprised non-officials (Non-officials, n = 102). The research was conducted during the transition between 2022 and 2023. Results: The findings revealed that officials in public regulatory bodies (regulators) overseeing network sectors in Poland are not free from behavioural influences. These include the certainty effect – leading to risk aversion (positive prospect), loss avoidance effect – causing risk-seeking behaviour (negative prospect) and the reflection effect in line with prospect theory. Additionally, they demonstrated the risk aversion effect stemming from the tendency to overestimate losses and underestimate gains, uncertainty effect, status quo effect, anchoring heuristic – the effect of asymmetric domination and the better-than-average effect, calibration effect and overconfidence effect, however, the prevalence of these effects varied. Furthermore, statistically significant differences in the occurrence of these behavioural effects were observed between officials of various regulatory bodies and the Non-experts group (78.6% of cases), which were more pronounced than the differences between the regulatory bodies themselves (21.4% of cases). Implications and recommendations: The research results underline the necessity of augmenting the conventional approach to regulation with an understanding of the behavioural factors that influence regulatory decision-making. Further research and the replication of the article’s findings are necessary, primarily due to the limitations of the research results. The experiments provided an opportunity to test the behavioural effects but they did not explore their relationship with the personality traits of the subjects. This aspect will be the focus of analysis in the forthcoming article. Additionally, future experiments may uncover other behavioural effects. Originality/value: The conclusions presented in this article contribute a unique perspective to the discourse on public regulation, drawing from empirical research results. This presents findings from a study involving officials from two distinct regulatory bodies. The novelty of research into the behavioural determinants of decisions made by officials in regulatory bodies expands the realm of regulatory research. This could potentially open new avenues for resolving regulatory dilemmas.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 43-55
Keywords: regulation; behavioural economics; heuristics; cognitive biases; Prospect Theory